Preclinical toxicological assessment of an α-galactosylceramide-adjuvanted mRNA cancer vaccine in Wistar Han rats and domestic pigs - Sofie Meulewaeter; Margo De Velder; Diethard Reckelbus; Kevin Mwangi; Thomas Ehouarne; Ilke Aernout; Yanou Engelen; Fellanza Halimi; Isis Van herteryck; Lobke De Bels; Valerie Redant; Louise De la Mane; et al. (Molecular Therapy: Methods & Clinical Development)
Galsome-NEO is a glycolipid-adjuvanted mRNA lipid nanoparticle (LNP) cancer vaccine encoding neo-epitopes for evaluation in a phase 1 study in patients with non-small cell lung cancer. To assess the safety of Galsome-NEO, a repeated-dose toxicity study was conducted in Wistar Han rats involving three intramuscular doses of 30 μg mRNA. A dose-escalation study in piglets tested three doses of 3, 15, and 100 μg mRNA. Rats showed a pronounced pro-inflammatory response, evidenced by cytokine secretion and an acute phase reaction. Clinical findings included temporary local reactions (maximum grade 3), elevated temperatures, and weight loss. In pigs, all doses were well tolerated. Blood analysis showed elevated alkaline phosphatase and decreased thrombocytes in rats, while pigs had reduced reticulocyte counts. Histology revealed hepatocyte vacuolation in rats and immune infiltration at injection sites in both species. In rats, blood and histology alterations resolved 3 weeks post dosing, except for immune infiltration in the connective tissue at injection sites in two females. Galsomes with mRNA encoding the Chlamydia trachomatis major outer membrane protein induced T cell responses in pigs. Natural killer T cell activation was observed in both species. These findings align with the safety data for the COVID-19 mRNA vaccine, Comirnaty, and demonstrate Galsomes’ potential in large animals.